Pendistribusian Zakat yang Tepat Untuk Mencapai Target SDG’s dan Target Global 2030 Studi Kasus BAZNAS DIY: Optimalization Zakat Distribution to Achieve SDG’s Targets and the 2030 Global Goals: A Case Study of BAZNAS DIY - Bani Idris Hidayanto; Mohammad Faozi; Nursya'bani Purnama; Edo Segara Gustanto (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
Zakat plays a strategic role in poverty alleviation and enhancing community welfare, aligning with the objectives of the Sustainable Development Goals (SDGs) and the 2030 global agenda. This study aims to analyze the effectiveness of zakat distribution by the National Zakat Agency (BAZNAS) of the Special Region of Yogyakarta (DIY) in supporting the achievement of specific SDG targets, particularly poverty reduction (SDG 1), quality education (SDG 4), and inclusive economic growth (SDG 8). Using a qualitative approach and a case study method, this research explores BAZNAS’ policies, programs, and the challenges in ensuring targeted zakat allocation. The findings indicate that optimizing zakat distribution based on the needs of mustahik (beneficiaries) and utilizing digital technology can accelerate the realization of the SDGs. Therefore, stronger synergy between BAZNAS, the government, and other stakeholders is essential to enhance the effectiveness and impact of zakat in supporting the global development agenda by 2030.